Morphological and anatomical responses to plant growth regulators of abscised shoot apices of grapevines (vitis) in in vitro culture and heat inactivation of grapevine fanleaf viruses in apices - Goussard, P. G. (Pieter Gabriel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD) -- Stellenbosch University, 1984.